(untitled) (Acta Scientiarum. Health Sciences, 2015)
Orthognathic surgery is widely used in the treatment of dento-maxillofacial deformities, which changes both the facial appearance and the pharyngeal airway space. The aim of this study was to evaluate cephalometric changes in the pharyngeal airway space before and after orthognathic surgery in patients with Class II and Class III malocclusions. The sample consisted of 38 lateral cephalograms, 17 of patients with Class II who had undergone mandibular advancement, and 21 of patients with Class III who had undergone mandibular setback. Cephalometric analysis of Arnett-Gunson FAB Surgery using Dolphin Imaging 11.5 evaluated point B’ and Pog’. Statistical analysis used Paired t-test at 5% significance level. The increase in the means of point B’ and Pog’ after mandibular advancement was not statistical. Similarly, the means of point B’ and Pog’ did not differ after mandibular setback. Thus, the pharyngeal airway space at the level of B’ and Pog’ kept constant pre and post orthognathic surgery for both Class II and Class III.